2019
DOI: 10.1016/j.ymgmr.2019.100454
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enzyme replacement therapy on clinical outcomes in male patients with Fabry disease: A systematic literature review by a European panel of experts

Abstract: BackgroundEnzyme replacement therapy (ERT) with recombinant human α-galactosidase has been available for the treatment of Fabry disease since 2001 in Europe and 2003 in the USA. Treatment outcomes with ERT are dependent on baseline patient characteristics, and published data are derived from heterogeneous study populations.MethodsWe conducted a comprehensive systematic literature review of all original articles on ERT in the treatment of Fabry disease published up until January 2017. This article presents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 196 publications
(737 reference statements)
3
98
0
23
Order By: Relevance
“…Enzyme replacement therapy with recombinant enzymes is the standard of care of treatment in Fabry disease (FD). Currently, two recombinant enzymes—agalsidase alfa (Replagal ® , Takeda Pharmaceutical Company, Ltd., Cambridge, MA, USA) and agalsidase beta (Fabrazyme ® , Sanofi Genzyme, Cambridge, MA, USA)—are available for patients with FD in the European Union, while only agalsidase beta is approved for use by US Food and Drug Administartion (FDA) in the USA [ 3 , 4 , 5 ]. Enzyme replacement therapy (ERT) with either of the recombinant enzymes has proven to be successful in mitigating the pathological effects and improving the quality of life in FD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme replacement therapy with recombinant enzymes is the standard of care of treatment in Fabry disease (FD). Currently, two recombinant enzymes—agalsidase alfa (Replagal ® , Takeda Pharmaceutical Company, Ltd., Cambridge, MA, USA) and agalsidase beta (Fabrazyme ® , Sanofi Genzyme, Cambridge, MA, USA)—are available for patients with FD in the European Union, while only agalsidase beta is approved for use by US Food and Drug Administartion (FDA) in the USA [ 3 , 4 , 5 ]. Enzyme replacement therapy (ERT) with either of the recombinant enzymes has proven to be successful in mitigating the pathological effects and improving the quality of life in FD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several treatments are available for FD. Three systematic literature reviews of Enzyme Replacement Therapy (ERT) have found significant decreases in GB3 accumulation and improvement in Fabry symptoms and quality of life for adult male [56], female [57] and paediatric Fabry populations [58]. ERT mimics the naturally-occurring α-Gal enzyme and breaks down GB3 throughout the body, including kidney cells, preventing further accumulation of GB3.…”
Section: Treatmentmentioning
confidence: 99%
“…Lastly, migalastat is expected, according to current and emerging evidence, to have better effects on cardiac outcomes and gastrointestinal symptoms than ERT, potentially improving both patient morbidity and quality of life. It should be acknowledged that further studies are required to investigate the long-term benefits of migalastat therapy, while some evidence is present for sustained activity of ERT to slow the decline in estimated glomerular filtration rate, and reduce/stabilize left ventricular mass and cardiac wall thickness [27].…”
Section: Migalastat: Role In the Therapy Of Fdmentioning
confidence: 99%